Exploring the burdens, experiences, and coping strategies of Malaysian family caregivers attending public rehabilitation centres during the COVID-19 pandemic - Mukhti, Muhammad Iqbal (2021)
Introduction: Stroke survivors are completely or partially reliant on their caretakers for routine daily activities. The existing chronic disease patient caregiving tasks are solely carried out by family carers, which were acknowledged to be more challenging in different dimensions. Whilst family caregivers are struggling to cope with the situation, the presence of the COVID-19 pandemic, which was started from Wuhan City, Hubei Province, China at the end of December 2019 and subsequently, spread to the various countries which eventually lead to the first case of COVID-19 reported in Malaysia at 25th January 2020 involving three Chinese peoples from Singapore that was entered to Malaysia via Johor. This situation certainly brought negative impacts or probably some positive impacts to the family caregivers. As the consequences, the reactions from family caregivers to compensate during the unprecedented crisis do matter as the benchmark of the caregiving role to sustain in the long-term run, hence establishing the health outcome of the stroke survivors in the future. To date, there has been deficient research published, particularly in qualitative design, on stroke family caregiving during the COVID-19 pandemic either internationally, or locally, Malaysia. Objectives: This study was aimed to explore the impact of the COVID-19 pandemic on stroke family caregivers attended the public rehabilitation centres in Kota Bharu, Kelantan with specific objectives derived; i) to explore the burdens and experiences faced by family caregivers in Kota Bharu, Kelantan during the COVID-19 pandemic while caregiving for the stroke patients and ii) to explore the coping strategies taken by family caregivers in Kota Bharu, Kelantan in dealing with the difficulties of stroke caregiving during the COVID-19 pandemic. Methodology: This qualitative study was used a phenomenological approach, conducted from November 2020 until June 2021, and designated from the in-depth interview guide research questions involving the recruitment of respondents until no new data generated. The total respondents of 13 family caregivers who cared for the stroke patients were selected whereby the stroke patients were registered under two public rehabilitation centres in Kota Bharu, Kelantan namely Hospital Raja Perempuan Zainab II (HRPZ II) and Hospital Universiti Sains Malaysia (Hospital USM). Purposive sampling with maximum variation technique was applied to identify the potential respondents representing different ages, sex, ethnicity, educational level, employment status, and relationships to the stroke patient through the list name of the study population. The interviews were set up during respondent’s follow-up appointments, established in the Kelantanese Malay dialect, and recorded via digital voice recorders. The six steps of thematic analysis were used to analyze the collected data in this study. Results: Three themes were identified with regards to the burdens and experiences faced by the family caregivers during the COVID-19 pandemic; i) worsening pre-existing issues, ii) emerging of new issues, and iii) less burdens and challenges. Whereas the subthemes for worsening pre-existing issues were; i) defect social life, ii) burdens of formal duty, and iii) tight appointment schedule. As for emerging of new issues were; i) defect in daily mobility, ii) changes in healthcare services, iii) limitation in strict Standard Operating Procedure (S.O.P), iv) extra role of cares on patient, v) constraints of supportive persons, and vi) financial constraints. On the other hand, the subthemes for less burdens and challenges as listed; i) improvement in hospital logistic issues and ii) strengthening the family bonding. Meanwhile, two themes were recognized as the coping strategies taken by the family caregivers in dealing with difficulties of caregiving during the COVID-19 pandemic; i) problem-focused engagement and ii) emotion-focused engagement. There were three subthemes beneath the problem-focused engagement theme; i) adapting the available support, ii) adaptation to the changes of healthcare services, and iii) permission to mobilize during the pandemic. In contrast, the emotion-focused engagement theme was listed the two subthemes that were; i) the obedience to the strict S.O.P of new norms and ii) passive response to the burdens and challenges of caregiving. Conclusions: Based on the findings from this study, we can have a better understanding of the evidence-based pandemic impact on the burdens and challenges faced by family caregivers and what were the coping strategies taken in dealing with the difficulties. It is best concluded in several ways; i) the pre-existing issues were worsening with the existence of the pandemic, ii) the emerging of new issues experienced with the execution of control measures taken by the government including travel restriction order, the implementation of S.O.P, the adaptation made by health sectors, and the chain effects of the pandemic upon external determinants that eventually affected the caregivers, and in contrast iii) the positive impacts derived indirectly from the action of measures taken. Meanwhile, as for coping strategies, both problem and emotion-focused engagement were rather focusing on the new issues that emerged as compared to solve the worsening pre-existing issues. Few attempts were taken under the problem-focused strategies but only a feeling of acceptance associated with the emotion-focused in facing the burden and difficulties during the pandemic.